1987
DOI: 10.1002/cyto.990080206
|View full text |Cite
|
Sign up to set email alerts
|

Application of pyronin Y(G) in cytochemistry of nucleic acids

Abstract: Chinese hamster ovary (CHO) cells or isolated nuclei were stained with pyronin Y (PY) and analyzed by absorption or fluorescence microscopy, as well as by flow cytometry. Specificity of the staining reaction was assayed by testing sensitivity of the stainable material to RNase or DNase. The colored complexes detected by light absorption in fixed cells stained with PY are nonfluorescent and are most likely the products of condensation of single-stranded (ss) RNA by PY; the poly(rA) and poly(rA,rG) are the most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0
24

Year Published

1991
1991
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(71 citation statements)
references
References 27 publications
1
44
0
24
Order By: Relevance
“…For example, the ability of a given ligand to enhance qacA transcription is related not only to how strongly it is bound by QacR but also to the relative affinity of the compound for its target site, the ease with which it gains entry into the cytoplasm, and the presence of MDR transporter homologues which may export the compound in question, thereby reducing its intracellular concentration. For the specific case of ethidium, proflavin, and pyronin Y, the discrepancy between their relatively low K d values, ranging from 0.81 to 5.15 µM, but only weak induction of P qacA in vivo (Table 2) may be related to the ability of these compounds to intercalate DNA (39). This property could result in a reduction in the effective intracellular concentrations of such QacR ligands due to their nonspecific sequestration in chromosomal DNA.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the ability of a given ligand to enhance qacA transcription is related not only to how strongly it is bound by QacR but also to the relative affinity of the compound for its target site, the ease with which it gains entry into the cytoplasm, and the presence of MDR transporter homologues which may export the compound in question, thereby reducing its intracellular concentration. For the specific case of ethidium, proflavin, and pyronin Y, the discrepancy between their relatively low K d values, ranging from 0.81 to 5.15 µM, but only weak induction of P qacA in vivo (Table 2) may be related to the ability of these compounds to intercalate DNA (39). This property could result in a reduction in the effective intracellular concentrations of such QacR ligands due to their nonspecific sequestration in chromosomal DNA.…”
Section: Discussionmentioning
confidence: 99%
“…18 Briefly, the isolated B-cell populations were fixed in 70% ethanol overnight, then resuspended in a solution of 2 g/mL Hst (Molecular Probes, Eugene, OR) and 4 g/mL PY (Polysciences, Warrington, PA) and measured by flow cytometry on a MoFlo equipped with UV laser (DakoCytomation). Since RNA staining with PY yields a continuous histogram without demarcation between positive and negative cells, 19 an arbitrary analysis window comprising about 90% of Bm1 and Bm2 subpopulations displaying minimal PY staining was used to designate the G 0 fraction in all experiments.…”
Section: Cell Cycle Fractionation With Hoechst and Pyronin Ymentioning
confidence: 99%
“…Consistent with their CD71 expression, an analysis of DNA/RNA content revealed that a majority of pro-GC tonsil cells are in a G 1 state at any given time. They were then fixed and stained with pyronin Y and Hoechst 33342 dye [18][19][20] (Figure 3). To our knowledge, this technique has not been previously reported for tonsillar B-cell subpopulations.…”
Section: Phenotypic Analysis Of a Novel B-cell Subpopulationmentioning
confidence: 99%
“…PY had been reported to specifically stain RNA in combination with DNA-specific stains, namely H342 (Tanke et al 1980, Shapiro 1981. Nevertheless, the considerable fluorescence-quenching of PY by increasing amounts of RNA added (due to the guanine bases, according to Darzynkiewicz et al 1987 andKapuscinski &Darzynkiewicz 1987) was a major limitation. The main interest in A 0 was the possibility of distinguishing between DNA and RNA based on the metachromatic properties of the dye (Darzynluewicz 1979, Darzynkiewicz et al 1983.…”
Section: Discussionmentioning
confidence: 99%